Teaching with Storytelling: An Investigation of Narrative Videos for Skills Training - Ladeira, Ilda; Cutrell, Ed (4th IEEE/ACM Conference on Information and Communication Technologies and International Development (ICTD) 2010, London, UK, IEEE, 2010)
We present a study on using storytelling for teaching skills to low-income workers in the developing world. Taking a cue from work on using dramatized stories and video to promote technology use and agricultural and HIV/AIDS education, we investigated storytelling’s ability for teaching low-literacy populations. We created a series of videos to teach domestic workers in urban India bed-making and vacuuming. We tested the effect on learning of a) embedding instructional content in narratives and b) adding motivational content on the benefits of learning these skills. We compared:1) instruction-only videos, 2) instructional videos book-ended with voice-overs describing skills’ benefits, 3) combined instructional and narrative videos showing no skill learning benefits; and 4) combined instructional and narrative videos which portray benefits for learning a skill. Narrative framing and motivational content each improved learning, but combining them resulted in dramatic improvement.